YESUS MENGULURKAN TANGAN DAN MENJAMAH - Petrus Christologus Dhogo (Ledalero Institute of Philosophy and Creative Technology (IFTK Ledalero), Indonesia, 2015)
For years HIV and AIDS were considered deadly viruses. Lacking appropriate knowledge about how these viruses develop made it more difficult to treat carriers, as they were once viewed as approaching death. Also, many thought that the virus was easily contagious (although it is not). Carriers were – and still are - marginalized and so could not maintain normal life in their communities. They were stigmatized more especially when the virus was viewed as the result of an un-controlled sex life. As “sinners” they had to pay for the sin they committed. This is pararell to the situation was faced by lepers at the time of Jesus. They were avoided, must not be touched; they were removed from the community. However, Jesus accepted lepers, touched them, and in accepting them broke through cultural and religious barriors. In Luke’s account (Luke 5:12-16) the leper does not seek a cure, but rather freedom from stigmatization (“made clean”). That is the “cure” that Jesus gave and what we can, and must, give today to HIV carriers. Kata-kata kunci: kusta, tahir, stigma, HIV, AIDS, Yesus, menjamah, mengulurkan, tangan, mentahirkan.